Dermatoscopy: Physics and principles - Balakrishnan Nirmal (Indian Journal of Dermatopathology and Diagnostic Dermatology, 2017)
Dermatoscopy is an in vivo noninvasive technique used to examine pigmented and amelanotic skin lesions. The technique is performed using a hand-held self-illuminating device called dermatoscope that visualizes features present under the skin surface that are not normally visible to unaided eye. The images from the dermatoscope can be digitally photographed or recorded for future reference. Nonpolarized dermatoscopy requires contact with the skin surface and interface fluid between glass and skin surface. Polarized light penetrates deeper than the nonpolarized light and does not require contact fluids.